Corrections: Red flags to screen for malignancy and fracture in patients with low back pain : systematic review - Downie, Aron; Henschke, Nicholas (The BMJ, 2014)
The authors of this Research paper ( BMJ 2013;347:f7095, doi:10.1136/bmj.f7095) have alerted us to a missing comma in the discussion section, which could lead to confusion. …
Gesehen am 18.12.2020